Influence of mould growth and outdoor exposure on the efficacy of attractive targeted sugar baits against Anopheles arabiensis in western Kenya - Nick O. Yalla; Jackline Kosgei; Frank Mechan; Daniel P. McDermott; Brian Polo; Seline Omondi; Elizabeth Omukunda; Eric Ochomo (PLoS ONE, 2025)
Introduction Attractive Targeted Sugar Baits (ATSBs) effectively target Anopheles mosquitoes in semi-arid, low-humidity climates. However, high humidity encourages mould growth on ATSB surfaces, and its effect on the efficacy of ATSBs against malaria vectors is yet to be determined. This study explored how mould growth affects the performance of ATSB version 1.2 by comparing mouldy stations from exposed environments to non-mouldy stations from protected settings through laboratory bioassays on the local malaria vector, Anopheles arabiensis. Methods One hundred ATSB stations were deployed in Asembo, Rarieda-Subcounty, Siaya County Six samples, consisting of three mouldy from exposed locations and three non-mouldy from protected locations were collected monthly for laboratory bioassays. These were tested alongside three new laboratory-kept ATSBs and two negative controls (water only and 77% sugar solution with water) to assess mosquito feeding and mortality over 48 hours. Results This study found that after 12 months of outdoor exposure, the mouldiest ATSBs from exposed locations showed a non-significant reduction in Anopheles arabiensis feeding rates compared to the least mouldy ATSBs from protected locations 57.42% (95% CI: 45.64–68.85) vs. 74.40% (95% CI: 64.56–82.50), (P = 0.062) respectively. Mosquito mortality significantly declined on mouldy ATSBs compared to laboratory controls 95.35% (95% CI: 92.23–97.48) vs. 98.70% (95% CI: 97.87–99.30), (P = 0.002) respectively. In contrast, protected (non-mouldy) ATSBs showed only a slight reduction in mortality compared to controls 95.94% (95% CI: 90.42–97.46) vs. 98.91% (95% CI: 97.67–99.60) respectively (P = 0.009). Conclusion This study provides evidence that environmental exposure post-deployment slightly reduced the efficacy of ATSBs in controlling Anopheles arabiensis, particularly beyond the recommended 6-month period. Although mould may have contributed to this reduction over 12 months, no significant difference was found between mouldy and non-mouldy ATSBs. However, mould invasion and community concerns highlight the need to replace mouldy stations to maintain effectiveness and safety.